Integrated Circuits on Fiber Substrates: State-of-the-Art System-on-Fiber Technologies for Smart Textiles and Wearables - Jin, Juyoung; Won, Jonghyun; Kim, Daegun; Arumugasamy, Shiva Kumar; Park, Sungjun; Kim, Tae‑Wook (Nano-Micro Letters, 2026)
System-on-fiber technologies have emerged as a promising platform for seamless integration sensing, signal processing, and communication functionalities within textile-compatible fiber architectures. Advances in materials science and microscale fabrication have enabled the development of multifunctional fibers that serve as active components in large-scale woven systems. These fibers can perform a range of functions including sensing, data processing, and even neuromorphic computing. Despite their potential applications in wearable electronics, healthcare monitoring, and human–machine interfaces, the practical implementation stays in its infancy. Key challenges include limitation in device encapsulation, interconnect reliability, and scalable manufacturing. This review systematically summarizes recent advancements in manufacturing approaches for fiber-based integrated electronics, device configurations, and integration strategies. Furthermore, key technological hurdles and future opportunities for achieving fully integrated autonomous fiber-based electronic systems are discussed. Highlights: 1 Presents a hierarchical overview of system-on-fiber (SoF) technologies, linking materials, fabrication methods, and device architectures from single-fiber electronics to system-level intelligent textiles. 2 Establishes a quantitative process–performance correlation framework, integrating AI-driven material optimization and comparative metrics (e.g., yield, endurance, and conductivity retention) across coating, thermal drawing, deposition, and spinning techniques. 3 Proposes a standardization and industrial translation roadmap outlining key steps testing certification, scalable manufacturing, and modular integration to move SoF systems from laboratory prototypes to consumer-ready smart textiles.